In Vivo Neutralization of Myotoxin II, a Phospholipase A2 Homologue from Bothrops asper Venom, Using Peptides Discovered via Phage Display Technology - Laustsen, Andreas Hougaard (2022)
Many snake venom toxins cause local tissue damage in prey and victims, which constitutes an important pathology that is challenging to treat with existing antivenoms. One of the notorious toxins that causes such effects is myotoxin II present in the venom of the Central and Northern South American viper, Bothrops asper. This Lys49 PLA2 homologue is devoid of enzymatic activity and causes myotoxicity by disrupting the cell membranes of muscle tissue. To improve envenoming therapy, novel approaches are needed, warranting the discovery and development of inhibitors that target key toxins that are currently difficult to neutralize. Here, we report the identification of a new peptide (JB006), discovered using phage display technology, that is capable of binding to and neutralizing the toxic effects of myotoxin II in vitro and in vivo. Through computational modeling, we further identify hypothetical binding interactions between the toxin and the peptide to enable further development of inhibitors that can neutralize myotoxin II.